Expansion of the dynamic strain field in 3D-printed structures using a hybrid modeling approach - Kodrič, Miha; Čepon, Gregor; Boltežar, Miha (Measurement : journal of the International Measurement Confederation, 2023)
The 3D printing of machine components is becoming an established technique. To ensure their robustness and longevity, it is crucial to numerically predict the dynamic response of these components in a variety of operating conditions. Dynamic properties are conventionally obtained in the form of displacement or strain-based response models. However, numerical modeling of the dynamic properties of 3D-printed structures can be a tedious task, mainly due to the complex geometry of the infill pattern and the influence of the printing parameters on the material and geometric properties. Alternatively, the dynamic properties can also be represented in the form of an experimental response model. This reflects the real dynamic properties, but is usually subject to measurement errors and has a low spatial resolution. To integrate the benefits of numerical and experimental response models, we propose a hybrid modeling approach with the System Equivalent Mixing method. The method was extended to a form that could integrate dynamic response models with different physical quantities (displacement and strain). The approach was then analyzed on a 3D-printed beam with a complex infill pattern, where an accurate expansion of the strain response to a high spatial resolution was demonstrated. •An alternative hybrid modeling of the dynamic properties of 3D-printed structures.•SEMM reformulation to integrate dynamic response models different physical quantities.•Strain response was measured with PVDF sensors and expanded to higher spatial resolution.